2017
DOI: 10.3758/s13414-017-1361-2
|View full text |Cite
|
Sign up to set email alerts
|

Headphone screening to facilitate web-based auditory experiments

Abstract: Psychophysical experiments conducted remotely over the internet permit data collection from large numbers of participants, but sacrifice control over sound presentation, and therefore are not widely employed in hearing research. To help standardize online sound presentation, we introduce a brief psychophysical test for determining if online experiment participants are wearing headphones. Listeners judge which of three pure tones is quietest, with one of the tones presented 180° out of phase across the stereo c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
255
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 353 publications
(262 citation statements)
references
References 23 publications
6
255
0
1
Order By: Relevance
“…We demonstrated that a robust measure of perceptual salience can be obtained without substantial constraints from a web-based mass-participant experimental platform. Online experimenting is gaining popularity within cognitive science (see Stewart et al, 2017 for a review), including in the auditory modality (Woods et al, 2017;Woods and McDermott, 2018).…”
Section: Crowd-sourced Saliencementioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that a robust measure of perceptual salience can be obtained without substantial constraints from a web-based mass-participant experimental platform. Online experimenting is gaining popularity within cognitive science (see Stewart et al, 2017 for a review), including in the auditory modality (Woods et al, 2017;Woods and McDermott, 2018).…”
Section: Crowd-sourced Saliencementioning
confidence: 99%
“…Since we were interested in the extent to which a relatively free listening environment can result in meaningful data, we did not impose constraints on sound delivery (e.g. Woods et al, 2017) or level (though it was suggested that the participants listen over headphones).…”
Section: Amazon Mechanical Turk Derived Subjective Saliencementioning
confidence: 99%
“…The noise root-mean-squared (rms) level was set to the maximum of the rms level of the experimental stimuli. Participants then completed a 'headphone check' task to help ensure that they were wearing headphones or earphones 46 . Finally, to eliminate participants who were not fully focused on the task, we included practice trails at the beginning of the experiment (described in more detail below).…”
Section: Experimental Procedures For Online Experimentsmentioning
confidence: 99%
“…Participants then performed a brief headphone check experiment [Woods et al 2017] intended to weed out participants who were ignoring the instructions to wear headphones or earphones. They next completed 20 practice trails in which they were asked to report whether they "heard the sound" or "didn't hear the sound" during the interrupting noise segment.…”
Section: Experiments 1 -Illusory Continuity For a Large Set Of Naturalmentioning
confidence: 99%
See 1 more Smart Citation